Knowledge and attitudes toward food sustainability among Kuwait University students - AlTarrah, Dana; Malik, Aisha; Nur, Amrizal (Frontiers in Sustainable Food Systems, 2024)
Transitioning toward sustainable food systems and sustainable diets is critical in reducing environmental impact and achieving the Sustainable Development Goals established by the United Nations General Assembly. This transition requires collaborative efforts across multiple stakeholders, including the general public’s knowledge and attitudes. To assess the knowledge and attitudes toward food sustainability, we carried out a cross-sectional study among Kuwait University students with a total of 278 participants aged ≥18 years (78% women and 22% men). A validated questionnaire was used for this study. Most respondents (>70%) recognized the concept of “local food” and “environmental impact.” The concept “green water-blue water” was least recognized among respondents (75%). Participants perceived that a sustainable diet was rich in vegetables, included plenty of fresh products, and was affordable. Participants (>66%) perceived a positive impact of meat and its derivatives toward sustainability, a misconception most common among men. Overall, participants with more knowledge about environmental concepts showed favorable attitudes toward a sustainable diet. Women showed more interest in changing their current dietary habits toward food sustainability. In conclusion, despite participants’ positive attitude toward food sustainability, lack of understanding persists, necessitating public health interventions aimed at educating consumers about sustainable diets and their impact on the environment.